2018
DOI: 10.1016/j.firesaf.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Flame extension lengths beneath a confined ceiling induced by fire in a channel with longitudinal air flow

Abstract: This paper investigates the length of flame extension for an impinging flame underneath the confined ceiling in a channel with longitudinal air flow. Previous works in this field have been primarily concerned with un-confined ceilings and no forced air flow conditions. Under longitudinal air flow conditions, the flame extension beneath the channel ceiling is non-symmetrical, that is, different in the upstream and downstream directions from the fire source. In this study, experiments were carried out with two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 23 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In tunnel fire scenarios, more attention has been paid to the characteristics of temperature change in the tunnel vault. Qiu et al [8] conducted full-scale tunnel fire tests and found that the temperature of the tunnel vault exhibited an exponential decay along the longitudinal direction. Lee et al [9] found that the temperature at the top of the tunnel near the fire source decreases with an increase in aspect ratio, and the reduction rate decreases with a decrease in heat loss.…”
Section: Introductionmentioning
confidence: 99%
“…In tunnel fire scenarios, more attention has been paid to the characteristics of temperature change in the tunnel vault. Qiu et al [8] conducted full-scale tunnel fire tests and found that the temperature of the tunnel vault exhibited an exponential decay along the longitudinal direction. Lee et al [9] found that the temperature at the top of the tunnel near the fire source decreases with an increase in aspect ratio, and the reduction rate decreases with a decrease in heat loss.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand an experimental study on temperature evolution inside the compartment with fire growth and flame ejection through an opening under external wind was considered by Hu, Longhua, et al [8]. They also considered the characterization of buoyant flow stratification and flame extension lengths in the tunnel fires [9,10]. Wan, Huaxian, et al [11] investigated a numerical study on the smoke back-layering length and inlet air velocity of fires in an inclined tunnel under natural ventilation with a vertical shaft.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is most important that the ventilation system is able to force the smoke movement in desired direction and with precisely determined velocity, called critical velocity [2]. Accurate determination of the value of critical velocity is a very important issue: it cannot be too low because it would not be able to force the desired flow direction, it cannot be too high as well because it would induce the fire growth, especially for HGV fires [4,5]. It could also disturb the stratification of the layers of clear air and smoke [6,7].…”
Section: Introductionmentioning
confidence: 99%